Quality of life and patient satisfaction at 7-year follow-up of antibiotic therapy vs appendectomy for uncomplicated acute appendicitis : secondary analysis of the appac randomized clinical trial - Viinikainen, Lauri (My University, 2020)
For more than a century, appendectomy has been the standard treatment for acute appendicitis and is still one of the most common emergency operations annually worldwide. Today, appendicitis is recognized to present in two forms, complicated and uncomplicated acute appendicitis. In the light of current research, it is known that antimicrobial therapy can be applied as an effective and safe treatment for uncomplicated acute appendicitis resulting in decreased morbidity, shorter sick leave, and major cost savings for the society compared with appendectomy. In our study, we evaluated the long-term effects of appendectomy and antibiotic therapy on quality of life and patient satisfaction in a secondary analysis of a randomized clinical trial (APPAC) comparing appendectomy and antibiotic therapy in the treatment of uncomplicated acute appendicitis. Between 2009 and 2011, 530 patients (aged 18 to 60 years) with a CT scan diagnosed uncomplicated appendicitis, were enrolled in the APPAC study and randomized to undergo appendectomy or antibiotic treatment. Antibiotic treatment consisted of intravenous ertapenem for three days, followed by per oral levofloxacin and metronidazole for seven days. In case of suspected appendicitis recurrence, antibiotic group patients underwent appendectomy without further imaging according to the study protocol. Of the 530 patients who were enrolled in the trial, 423 (80 %) were available for a phone interview at median follow-up of seven years. The interview was conducted by using a standardized QOL (Quality of life) EQ-5D-5L -question set consisting of five questions currently measuring quality of life and satisfaction, plus two separately added questions mapping whether patients would again choose the same treatment based on their experience and the potential reasons for their treatment choice. There was no significant difference in QOL between the patients undergoing appendectomy and the patients receiving successful antibiotic treatment. However, there was a significant difference in patient satisfaction between the treatments; patients undergoing appendectomy were more satisfied with their treatment than those in the antibiotic group who had to undergo surgery for recurrence of the disease. Patients in antibiotic group with successful antibiotic therapy without recurrence had no difference in the satisfaction rates compared with the appendectomy group. In the treatment of uncomplicated appendicitis, long-term QOL is similar between the two treatments, but the lower patient satisfaction in the antibiotic group patients undergoing surgery indicates that predictive parameters for disease recurrence should be actively assessed. Despite the lower satisfaction rate in the antibiotic group patients undergoing surgery, a significant proportion of patients with recurring disease would still re-select antibiotic therapy to avoid surgery. As antibiotic therapy is a safe and effective treatment for uncomplicated appendicitis, the choice of the optimal therapy should be a joint decision with the patient, considering the benefits and risk of the various treatment options.
Keywords: appendicitis, appendectomy, antibiotic treatment, quality of life